2014
DOI: 10.1007/s11418-014-0839-7
|View full text |Cite
|
Sign up to set email alerts
|

Anethole and eugenol reduce in vitro and in vivo leukocyte migration induced by fMLP, LTB4, and carrageenan

Abstract: The aim of this study was to investigate the effect of anethole (AN) and eugenol (EUG) on leukocyte migration using in vitro chemotaxis and in situ microcirculation assays. BALB/c mice were used for the in vitro chemotaxis assay, and Wistar rats for the in situ microcirculation assay. We evaluated (a) the in vitro leukocyte migration in response to chemotactic factors (formyl-methionyl-leucyl-phenylalanine [fMLP] and leukotriene B4 [LTB4]) and (b) the rolling, adhesion, and migration of leukocytes induced by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…Since EST treatment did not affect the leukocytes viability evaluated by cytotoxicity assay at all concentrations tested (data not shown), our data suggest that the direct effect of EST on inhibition of leukocyte migration does not seem to be related to toxic effects (e.g., cell death). Recent study performed in our laboratory showed that both anethole and eugenol (structural analog of EST) reduced leukocyte migration induced by fMLP, probably by inhibitory effects of these compounds on synthesis/release cytokines [23]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since EST treatment did not affect the leukocytes viability evaluated by cytotoxicity assay at all concentrations tested (data not shown), our data suggest that the direct effect of EST on inhibition of leukocyte migration does not seem to be related to toxic effects (e.g., cell death). Recent study performed in our laboratory showed that both anethole and eugenol (structural analog of EST) reduced leukocyte migration induced by fMLP, probably by inhibitory effects of these compounds on synthesis/release cytokines [23]. …”
Section: Resultsmentioning
confidence: 99%
“…Recently it was demonstrated by our research group that anethole decreased the acute inflammatory process by inhibiting some mediators such as NO, PGE 2 , TNF, IL-1 β , and IL-17 and it was also able to inhibit leukocyte migration in vitro and in vivo [7, 9, 23]. Indeed, EST presented inhibitory activity on paw edema induced by TNF- α in mice [10].…”
Section: Resultsmentioning
confidence: 99%
“…They have also found that the oil of star anise is stimulant, stomachic, carminative, mildy expectorant and diuretic. It has been also reported that the fruit of the plant has been used in traditional medicine for treatment of stomach aches, vomiting, rheumatic pain, insomnia and skin inflammation (Sung et al, 2012;Wang et al, 2011;Estevao-Silva et al, 2014;Park et al, 2015). Aly et al (2014) mentioned that its fruit is an important traditional Chinese medicine as well as a commonly used spice.…”
Section: Introductionmentioning
confidence: 99%
“…This oil has demonstrated to possess different biological properties, such as antimicrobial, analgesic, anti-inflammatory, antioxidant, antimutagenic, and anticarcinogenic effects [3, 12]. Recent in vivo studies have explored the potential anticancer property of eugenol, demonstrating the induction of apoptosis in several cancer cell lines from animal tumor models [4, 13].…”
Section: Introductionmentioning
confidence: 99%